Perfectionism Classes and Aggression in Adolescents - Ruiz-Esteban, Cecilia; Méndez, Inmaculada; Fernández-Sogorb, Aitana; Álvarez Teruel, José Daniel (Frontiers in Psychology, 2021)
Some of the components of perfectionism produces a variety of problems such as interpersonal hypersensitivity and hostility that may be associated with aggression behavior during adolescence. This study aims to identify classes of adolescents depending on their levels of Perfectionistic Strivings (PS) and Perfectionistic Concerns (PC) as well as to examine whether there are significant differences in the manifestations of the four components of aggression behavior (i.e., anger, hostility, physical aggression and verbal aggression) between them. A total of 1074 high school students from various educational centers participated in this study (M = 14.78, SD = 1.84). The Child-Adolescent Perfectionism Scale and the Aggression Questionnaire short form were used. The Latent Class Analysis identified three classes of adolescent perfectionism: a) Non-Perfectionists (low PS and PC), b) Maladaptive Perfectionists (high PS and PC), and c) Adaptive Perfectionists (moderate PS and PC). Results revealed significant differences between classes regarding the different manifestations of aggression. Maladaptive Perfectionists and Adaptive Perfectionists reported, respectively, the highest and lowest levels of aggression behavior. This study assists in educational programs to prevent conflicts related to school violence through emotional adjustment.